USE OF THE "LEAN AND SIX SIGMA" METHODOLOGY IN THE SYSTEM OF SAFETY-ORIENTED MANAGEMENT OF HEALTH CARE INSTITUTIONS (Development Service Industry Management, 2023)
The modern realities of the functioning of health care institutions necessitate the transformation of approaches to their management. It should be noted that for more than 5 years, medical reform has been ongoing in Ukraine, the purpose of which is to change approaches to the financing system and to form a "patient-oriented" economic and organizational model of health care institutions. The new model of the operation of medical institutions is focused on achieving a comprehensive result, which includes the provision of quality medical services with the most effective use of the resources of the health care institution and allows the formation of an appropriate management system aimed at development.The purpose of the study is to develop proposals for the use of the "Lean and Six Sigma" methodology in the concept of safety-oriented management of domestic health care institutions.The transformation of approaches to the management of health care institutions necessitates a radical rethinking of the conceptual foundations of the functioning of their internal economic mechanism, under which the management of their economic systems increasingly acquires the characteristics not of "classic budget institutions as the main managers of budget funds", but of full-fledged participants in the market for the provision of medical services, which is characterized by competition, cost optimization, anti-crisis and security-oriented management. These issues are especially relevant in the context of overcoming the consequences of the COVID-2019 pandemic and the military aggression of the Russian Federation, which caused a significant burden on the domestic health care system. Therefore, domestic scientists face the task of researching the international experience of the functioning of medical institutions in the conditions of overcoming challenges and threats caused by various pandemics, man-made accidents, natural disasters and military operations, which leads to a significant burden on the health care system due to the increase in the number of visits to doctors and hospitalization.The analysis of the international experience of the functioning of health care institutions shows the effective use of the "Lean and Six Sigma" methodology, which involves the application of the ideas of the "thrifty" health care system in order to minimize non-productive losses in each business process and their continuous improvement.
Keywords: Lean Six Sigma; business processes; healthcare facilities; safety-oriented management